Detection of tumor antigens and tumor-antigen specific T cells in NSCLC patients: Correlation of the quality of T cell responses with NSCLC subtype - Palata, Ondrej; Podzimkova Hradilova, Nada; Mysiková, Dagmar; Kutna, Beata; Mrazkova, Hana; Lischke, Robert; Spisek, Radek; Adkins, Irena (Immunology letters, 2020)
Allogeneic cancer cell lines serve as universal source of tumor-associated antigens in cancer vaccines. Immunogenic high hydrostatic pressure-killed cancer cells derived from cell lines can be used for the generation of dendritic cell (DC)-based active cellular immunotherapy of non-small cell lung cancer (NSCLC). We investigated the expression of 12 known NSCLC tumor-associated antigens (TAA) (CEA, MAGE-A1, MAGE-A3, MAGE-A4, PRAME, hTERT, HER2, MUC1, Survivin, STEAP1, SOX2 and NY-ESO-1) in 6 NSCLC cell lines as candidates for the generation of DC-based lung cancer vaccine. We showed that the selected antigenic profile of these cell lines overlaps to various degrees with that of primary NSCLC tumors (n = 52), indicating that 4 out of 6 NSCLC cell lines would be suitable for DC-based vaccine generation. We further investigated the presence of TAA-specific T cells in blood of NSCLC patients (n = 32) using commercially available peptide mixes in an in vitro stimulation assay. IFN-γ+CD8+ and IFN-γ+CD4+ T cell responses to all antigens were detected in NSCLC patients. Interestingly, despite higher TAA expression in squamous cell carcinoma (SCC) the responsiveness of patients' T cells to stimulation was significantly lower in SCC patients than in adenocarcinoma (AC) patients. This suggests qualitative differences in T cell functionality between NSCLC subtypes. Based on this study, and in order to maximize the amount of treatable patients, we selected a mix of H520 and H522 NSCLC cell lines for DC-based vaccine preparation. We also established a minimal panel of antigenic peptide mixes (CEA, hTERT, PRAME, HER2) for immunomonitoring of T cell responses during the DC-based lung cancer immunotherapy in Phase I lung cancer clinical trial (NCT02470468).
Keywords: Female; cytotoxické T-lymfocyty; Cell Line, Tumor; nemalobuněčný karcinom plic; Antigens, Neoplasm; ženské pohlaví; Dendritic Cells; nádory plic; dendritické buňky; antigenní specifita receptorů T-buněk; Cancer Vaccines; Immunotherapy; lidé; staging nádorů; T-Cell Antigen Receptor Specificity; T-lymfocyty; protinádorové vakcíny; T-Lymphocytes, Cytotoxic; Male; imunoterapie; Aged; Carcinoma, Non-Small-Cell Lung; Lung Neoplasms; lidé středního věku; senioři; mužské pohlaví; T-Lymphocytes; antigeny nádorové; Middle Aged; Neoplasm Staging; nádorové buněčné linie; Humans